Rotating flow over a vertical Riga plate with ramped heating using transformer oil - Ali, Farhad; Afshana, Gul; Sheikh, Nadeem Ahmad; Khan, Ilyas (Zeitschrift für angewandte Mathematik und Mechanik, 2024)
The present study explores the electrohydrodynamic flow of Casson nanofluid over a vertical Riga plate within a rotating frame, incorporating a ramped wall temperature (RWT). Transformer oil, selected as the base fluid for its engineering applications, is infused with dispersed graphene nanoparticles to form the nanofluid. The analysis further accounts for the effects of radiation, chemical reactions, and porous media. By employing dimensionless variables, the governing system of ordinary differential equations, subject to specific boundary conditions, is transformed. The Laplace transform method is then applied to determine the distributions of temperature, concentration, and velocity. The effects of various physical parameters on velocity, temperature, and concentration profiles are discussed in the physical sense. Results showed that adding 4% graphene nanoparticles considerably increases the rate of heat transfer from transform oil to 7.88% in both cases of RWT and isothermal wall temperature (IWT). Graphene nanoparticles enhance the life of transformers by improving thermal conductivity and decreasing oxidation resistance in the transformer oil, which eventually leads to greater heat dissipation and less degradation.